O lema aprender a aprender na literatura de informática educativa - Ferreira, Benedito de Jesus Pinheira; Duarte, Newton [UNESP] (FapUNIFESP (SciELO), 2012)
This paper makes a characterization of pedagogical conceptions found in the educational informatics literature in Brazil as well as in the work of Seymour Papert given the undeniable influence of this author in that literature. We identified a strong hegemony in this field of learning-to-learn pedagogy by means of constructivism, constructionism, learning projects and pedagogy of competencies among others. We make a critical analysis of these trends in light of the historical-critical pedagogy pointing to a number of aspects that need further discussion, highlighting the problematic opposition between teaching and learning.

Este artigo faz uma análise das concepções pedagógicas presentes na literatura nacional de informática educativa, assim como na obra de Seymour Papert, dada a influência incontestável desse autor na referida literatura. Identificamos nesse campo uma forte hegemonia das pedagogias do aprender a aprender, pela via do construtivismo, do construcionismo, dos projetos de aprendizagem e da pedagogia das competências, entre outros. Fazemos uma análise crítica dessas tendências à luz da pedagogia históricocrítica, apontando um conjunto de aspectos que carecem de análise aprofundada, com destaque para a problemática contraposição entre ensino e aprendizagem.
The slogan learning to learn in the educational informatics literature
Keywords: Educational informatics; Historical-critical pedagogy; Learning to learn